Ensino de Filosofia: currículo, realidade de contexto e formação de professores - Moraes, Simone Becher Araujo (Linguagens & Cidadania, 2017)
The objective of this work is to promote a brief reflection on what is understood about the teaching of philosophy and its possibility in view of the various aspects of the reality of our country, discussing one of the main criteria for the construction of a curriculum that is minimally adequate it’s "target audience", which are teenagers, whose main feature are: the search for answers to "immaturity" and questions about life, authority, and about himself.